Constitutionalization of arbitration in Peru: some considerations around relationship among arbitration, Constitution, fundamental rights and Rule of law - Bustamante Alarcón, Reynaldo (2013)
This article point out the progressive enrichment by which fundamental rights concept have gone through, providing to holders—government and individuals— not only rights, liberties, powers and immunity but also the obligation to respect, defend, guarantee and promote all them regardless the conduct displayed by the holder in this field. With this in mind, the author examines arbitration definition and main characteristics, highlighting its constitutional dimension proposing a systematic reading in accordance with fundamental rights.